Tuberous legumes - back from the brink - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
First International Symposium on Tuberous Legumes was held in Guadeloupe from 21 to 24 April 1992